MOF-based catalysts for CO2 reduction via photo-, electro-, and photoelectrocatalysis: a review - Mahmood Riyadh Atta; Akram Fadhl Al-Mahmodi; Baker Nasser Saleh Al-Dhawi; Md. Maksudur Rahman Khan (Academia Green Energy)
The increasing levels of carbon dioxide (CO2) in the atmosphere have driven global efforts to find sustainable and effective reduction technologies to mitigate climate change. Among these, Metal–Organic Framework (MOF)-based catalysts have emerged as a promising solution due to their high surface area, tunable porosity, and ability to incorporate active metal sites. There is a gap in the literature, specifically in understanding the advancement of MOF-based catalysts in these three technologies. The objective of this paper is to provide a comprehensive review of the latest developments in MOF-based photocatalysis, electrocatalysis, and photoelectrocatalysis for CO2 reduction. The literature analysis findings showed that in PC MIL-101(Cr)-Ag produced the highest methane rate, Au10@ZIF-67 produced the highest methanol rate, while formic acid is the major product in EC, produced especially by Zr-MOF catalysts, and Ti/TiO2NT-ZIF-8 showed outstanding PEC performance. This review highlights the catalytic performance of various MOF structures, focusing on the influence of synthesis methods, metal centers, and operating conditions on product selectivity and efficiency. While MOF-based catalysts hold immense potential, challenges related to their stability, scalability, and product selectivity must be addressed for industrial applications. Future research should focus on optimizing these systems for enhanced durability, cost effectiveness, and energy efficiency to meet the growing demand for sustainable energy solutions.